Ageing, gender politics and masculinities: reflections on collective memory work with older men. Issue 2 (11th June 2018) - Blake, Vic; Hearn, Jeff; Jackson, David; Barber, Randy; Johnson, Richard; Luczynski, Zbyszek
Abstract : Purpose: The purpose of this paper is to reflect on the process of participating in a long-term collective memory work group of older men, focusing on the making/unmaking of older men and masculinities, and the potential of memory work with older men. Design/methodology/approach: Participant review and reflection on collective memory work with a group of older men. Findings: Collective memory work provides a novel way to explore ageing, gendering, men, and masculinities. Its potential for working with older men is examined critically in relation to gender politics, power and (in)equalities, interconnections and contradictions of men's ageing and gendering, the personal and the political, as well as working with older men more generally, including those in transition and crisis. Originality/value: There is little previous writing on this approach to ageing, men, and masculinities. The paper aims to stimulate wider applications of this approach.